PENGARUH METODE GALLERY WALK TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN IPA TERPADU DI KELAS VIII SMP NEGERI 1 LAHUSA TAHUN PEMBELAJARAN 2021/2022 - Santimbalaki Buulolo (Universitas Nias Raya, 2022)
Background based on behind problem that student depend on teaching as source main information about lesson, student reluctant ask on teaching so if there is this not yet undertood so that knowledge this have student depends for what this given teaching, teaching subjects biology not yet once apply method learning galley walk seen student not enough interested study, even student no focus when teaching explain theory learning. Study this aim knowing influence method learning galley walk to interest study student in class VIII Junior High School country 1 Lahusa Year learning 2021/2022. Type study is quantitave which character deskription. . Populaton in study is VIII whereas sample study is student in class VIII Junior High School country 1 Lahusa as experiment. Data study this analyzed whit use test normality and tes hypothesis with use aplication statistical product and service slution version 20. Result the value of sig. (2-tailed) is 0.021 < 0.05, it is known that t count -2.433 < t table 2.03452, it can be concluded that the data is normally distributed so that students have an interest in learning in participating in learning activities through the gallery walk method. Suggestions from researchers are 1) The teacher should use the gallery walk learning model in learning activities because it makes students study hard and there is an attraction obtained by studying Science-Biology 2) The next researcher should carry out this research with a wider scope